2020
DOI: 10.1002/ppsc.202000243
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Black‐Phosphorus‐Nanosheet‐Based Nanoagent for Enhanced Chemo‐Photothermal Therapy

Abstract: Black phosphorus nanosheet (BPNS) is a promising multifunctional material in the biomedical field with biodegradability and low side effects, however its features are always weakened severely owing to its poor stability. Here, a novel method is developed for improving the defect of BPNS based on the effective protection of poly(lactic‐co‐glycolic acid) (PLGA), which preserves the stable photothermal therapy (PTT) effect of BPNS and biodegradability of the material. Meanwhile, doxorubicin (DOX) is loaded on BPN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…In addition, several studies have confirmed that they exhibit biodegradable and compatible nature to avoid toxicity in vivo. [253,[259][260][261] These properties give BPNSs great potential in the field of biomedicine. At present, BPNSs have become one of the hottest 2D nanomaterials for the treatment of AD.…”
Section: D Nanomaterialsmentioning
confidence: 99%
“…In addition, several studies have confirmed that they exhibit biodegradable and compatible nature to avoid toxicity in vivo. [253,[259][260][261] These properties give BPNSs great potential in the field of biomedicine. At present, BPNSs have become one of the hottest 2D nanomaterials for the treatment of AD.…”
Section: D Nanomaterialsmentioning
confidence: 99%
“…Articles actively used in the preparation of this review article are cited in the reference section. 3,4,13–21,23–28,30–137 The data was selected in a time-blind manner, i.e. dependent only on the suitability of the data without prioritizing the year the data was published.…”
Section: Literature Review and Database Structurementioning
confidence: 99%
“…As it has been previously described in section 2, other different processes have been explored to protect NBP; namely physical and chemical strategies. 72 Polymer capping such as poly(lactic-co-glycolic acid), 73 or polyethylenimine (PEI) 74 have also been used to prolong the shelf life of the material and for the design of efficient phototherapeutic/drug delivery NBP-based platforms. In conclusion, while the surface of GO is chemically modified to enhance its biodegradation ability, 58,75 NBP is normally functionalised to slow down its degradation rate, making it a more stable material.…”
Section: Nanoscale Advances Accepted Manuscriptmentioning
confidence: 99%